Neurons in the thalamic reticular nucleus are selective for diverse and complex visual features - Vaingankar, Vishal; Soto Sanchez, Cristina; Wang, Xin; Sommer, Friedrich T.; Hirsch, Judith A. (Frontiers in Integrative Neuroscience, 2012)
All visual signals the cortex receives are influenced by the perigeniculate sector of the thalamic reticular nucleus, which receives input from relay cells in the lateral geniculate and provides feedback inhibition in return. Relay cells have been studied in quantitative depth; they behave in a roughly linear fashion and have receptive fields with a stereotyped centre-surround structure. We know far less about reticular neurons. Qualitative studies indicate they simply pool ascending input to generate nonselective gain control. Yet the perigeniculate is complicated; local cells are densely interconnected and fire lengthy bursts. Thus, we employed quantitative methods to explore the perigeniculate, using relay cells as controls. By adapting methods of spike-triggered averaging and covariance analysis for bursts, we identified both first and second order features that build reticular receptive fields. The shapes of these spatiotemporal subunits varied widely; no stereotyped pattern emerged. Companion experiments showed that the shape of the first but not second order features could be explained by the overlap of On and Off inputs to a given cell. Moreover, we assessed the predictive power of the receptive field and how much information each component subunit conveyed. Linear-nonlinear models including multiple subunits performed better than those made with just one; further each subunit encoded different visual information. Model performance for reticular cells was always lesser than for relay cells, however, indicating that reticular cells process inputs nonlinearly. All told, our results suggest that the perigeniculate encodes diverse visual features to selectively modulate activity transmitted downstream